Sirenomelia in Dicephalic parapagus twins discordant for anencephaly and spina bifida. - Shrestha, Tripti; Baral, Gehanath; Sedhain, Nesuma (Nepal Journal of Obstetrics and Gynaecology, 2020)
An extremely rare case of sirenomelia in dicephalic parapagus twins discordant for anencephaly and spina bifida that was diagnosed after birth is presented. High incidence of congenital anomalies both with sirenomelia and parapagus twins independently make the prognosis much worse, with additional neural tube defect rendering it almost incompatible with life. Termination of pregnancy is advised when diagnosed in utero. Key words: anencephaly, dicephalic parapagus, spina bifida, sirenomelia